1995
DOI: 10.1007/bf01876095
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation ofVerticillium dahliae populations on the basis of vegetative compatibility and pathogenicity on cotton

Abstract: Complementary auxotrophic nitrate-nonutilizing (nit) mutants were used to investigate vegetative compatibility within 27 strains of Verticillium dahliae isolated from several hosts originating from Africa, Asia, Europe and the United States. Using about 500 nit mutants generated from these strains, three vegetative compatibility groups, 1, 2 and 4, were identified. Simultaneously, virulence of each strain was assessed on cultivars of Gossypium hirsutum, G. barbadense and G. arboreum, based upon Foliar Alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 29 publications
7
90
2
Order By: Relevance
“…On the other hand, considering VCGs as fully genetically isolated groups may be a strict statement. In fact, the existence of weak complementation and formation of heterokaryons between isolates belonging to different VCGs (or certain subgroups), or even between different Verticillium species, has been described (Daayf et al 1995;Hiemstra and Rataj-Guranowska 2003;Joaquim and Rowe 1990;Strausbaugh et al 1992). This may suggest the existence of a continuum of genetic variation surpassing the genetic barrier of the VCG.…”
Section: Pathogenicity Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, considering VCGs as fully genetically isolated groups may be a strict statement. In fact, the existence of weak complementation and formation of heterokaryons between isolates belonging to different VCGs (or certain subgroups), or even between different Verticillium species, has been described (Daayf et al 1995;Hiemstra and Rataj-Guranowska 2003;Joaquim and Rowe 1990;Strausbaugh et al 1992). This may suggest the existence of a continuum of genetic variation surpassing the genetic barrier of the VCG.…”
Section: Pathogenicity Groupsmentioning
confidence: 99%
“…The study of VCGs has traditionally served to explore genetic diversity in V. dahliae populations from the perspectives of geographical origin and/or plant host provenance of isolates. Currently, VCG1 (A and B), VCG2 (A and B), and VCG4 (A and B) (Chen 1994;Daayf et al 1995;Dobinson et al 2000;Rowe 1990, 1991;andKorolev et al 2000, 2001;Strausbaugh et al 1992;Zhengjun et al 1998) are fully accepted. The differentiation into subgroups A and B is based on the frequency and vigor of nit mutant complementation (Joaquim and Rowe 1991;Strausbaugh 1993).…”
Section: Pathogenicity Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that strains of similar pathogenicity belong to the same VCG (Strausbaugh et al, 1992;Daayf et al, 1995;Dervis et al, 2009). Strains belonging to Fusarium oxysporum f. sp.…”
Section: Vegetative Compatibility (Or Incompatibility) and Vegetativementioning
confidence: 99%
“…The cotton defoliating strain T9 (the original defoliating pathotype from cotton in California) belongs to subgroup VCG1A (Bell 1994). Only isolates of this subgroup caused severe defoliation of cotton in previous studies (Daayf et al 1995;Korolev et al 2008). Thus, isolates strongly compatible with T9 (or strongly compatible with other testers) may be assigned to VCG1A (Korolev et al 2008).…”
mentioning
confidence: 99%